Considerations regarding public debt increase - LUIS DOMINGO LAINO (Población y Desarrollo, 2016)
Public Debt balance, which was of USD 2.747 million in December 2011, increased to 6.114 million in the first semester of 2016, as a con-sequence of an indebtedness increase policy initiated by the administration that took over the government in June 2012 and was later continued by the administration that followed in August 2013. In a four year lapse, public debt doubled, signifying an increase in debt burden from a level of 10,9% of the Gross Domestic Product (GDP) in 2011 to a 22,5% of the GDP in the first semester of 2016. The present article poses considerations regarding this situation, that in further years will require major tributary incomes or new indebtedness to Paraguay in order to cover services of the assumed debts.